Constitución de la República de Surinam de 1987 con las reformas de 1992 - Centro de Estudios Sudamericanos (2008)
Preamble: We, the people of Suriname, inspired by the love for this Country and the belief in the power of the Almighty and guided by the centuries-long struggle of our people against colonialism, which was terminated by the establishment of the Republic of Suriname on 25 November 1975, taking the coup d'ètat of 25 February 1980 and the consequences thereof, conscious of our duty to combat and to prevent every form of foreign domination, resolved to defend and protect the national sovereignty, independence and integrity, assured of the will to determine our economic, social and cultural development in full freedom convinced of our duty to honor and to guarantee the principles of freedom, equality and democracy as well as the fundamental rights and freedoms of man, inspired by a civic spirit and by the participation in the construction, expansion and maintenance of a society that is socially just, determined to collaborate with one another and with all peoples of the world on the basis of freedom, equality, peaceful coexistence and international solidarity. (Párrafo extraído del texto a modo de resumen)